Short-Term Steroid-Induced Central Serous Chorio-Retinopathy in a Patient with Laser Foveal Burn: Doi: 10.36351/pjo.v37i1.1151 - Memon, Nasir Ahmed; Memon, Abdul Sami; Ahmed Bhutto, Israr; Mahar, Pir Salim (Pakistan Journal of Ophthalmology, 2020)
Oral intake of steroids has been associated with central serous chorio-retinopathy (CSCR) for long time. We report a 23 years old male who had exposure to green laser pointer after which he developed laser maculopathy. The treating ophthalmologist started oral steroids with patient developing CSCR in his left eye. He was referred to our retina clinic for further evaluation. On examination his vision was 6/6 Part in his right eye and 6/9 Part in his left eye. His dilated fundus examination revealed small foveal scar in his right eye and dull foveal reflex in his left eye. On OCT he had laser maculopathy in right eye and left fundus findings coincided with diagnosis of central serous chorio-retinopathy (CSCR). Patient was asked to discontinue his deltacortil tablets. The patient went back to his primary ophthalmologist who restarted deltacortil tablets. CSCR developed again. Key Words: Maculopathy, burn, Steroids, Central Serous Chorio-retinopathy.